Week 96 efficacy and safety of darunavir/ritonavir monotherapy vs. darunavir/ritonavir with two nucleoside reverse transcriptase inhibitors in the PROTEA trial1. Issue 1 (9th June 2016) - Girard, PM; Antinori, A; Arribas, JR; Ripamonti, D; Bicer, C; Netzle‐Sveine, B; Hadacek, B; Moecklinghoff, C
Abstract : Objectives: PROTEA is a randomized controlled trial to assess the efficacy and safety of darunavir/ritonavir (DRV/r) monotherapy as an alternative to triple therapy. Methods: Patients fully suppressed on first‐line antiretrovirals (viral load < 50 HIV‐1 RNA copies/mL) were switched to DRV/r 800/100 mg once daily, either as monotherapy ( n = 137) or with two nucleoside reverse transcriptase inhibitors (NRTIs) ( n = 136). Treatment failure was HIV‐1 RNA level ≥ 50 copies/mL at week 96 or discontinuation of study treatment [Food and Drug Administration (FDA)snapshot algorithm]. Results: Patients were mainly male and white, with mean age 44 years. In the primary efficacy analysis, the percentage of patients with HIV‐1 RNA < 50 copies/mL by week 96 [intent to treat (ITT)] was lower in the DRV/r monotherapy arm (103 of 137 patients; 75%) than in the triple therapy arm (116 of 136 patients; 85%) [difference −10.1%; 95% confidence interval (CI) −19.5, −0.7%]. In the switch‐included analysis, monotherapy was noninferior to triple therapy. In a post hoc analysis, for patients with nadir CD4 count ≥ 200 cells/μL, rates of HIV‐1 RNA suppression were 82 of 96 patients (85%) in the DRV/r monotherapy arm and 88 of 106 patients (83%) in the triple therapy arm. No treatment‐emergent primary protease inhibitor mutations were detected in either arm. The frequency of adverse events was similar in the two arms; however, one patient in the monotherapy arm was hospitalized with HIV encephalitis and elevated cerebrospinal fluid HIV‐1 RNA. Conclusions: In this study, in patients with HIV‐1 RNA < 50 copies/mL at baseline, switching to DRV/r monotherapy showed lower efficacy vs. triple therapy at week 96 in the primary ITT switch‐equals‐failure analysis, particularly in patients with CD4 counts < 200 cells/ μ L.